Discovering superconductivity : an investigative approach - Ireson, Gren. (The Atrium, Southern Gate, Chichester, West Sussex, UK : Wiley, 2012)
"The highly-illustrated text will serve as excellent introduction for students, with and without a physics background, to superconductivity. With a strong practical, experimental emphasis, it will provide readers with an overview of the topic preparing them for more advanced texts used in more advanced undergraduate and post-graduate courses.The book will feature a series of practical, investigative, activities which can be used as tutor demonstrations or, more usefully, as student lab' exercises. All of the activities have been designed and tested by the author and colleagues and are designed to be as low cost as possible in order to promote whole class use.Contents: 1. Introduction Resistivity and Conduction in metals History of Superconductivity2. Superconductivity An explanation of superconductivity The Meissner-Ochsenfeld Effect Diamagnetic Effects Persistence of current Type I and Type II Superconductors Flux Pinning3. Superconducting Materials Low Temperature Superconductors Organic Superconductors High Temperature Superconductors4. Applications Medical Imaging CERN Maglev TrainsPractical Activities - will be integrated into the text; a-f in section 2 and f and g in section 4 a. Diamagnetism 1: pyrolitic graphite b. Diamagnetism 2: Bismuth c. Diamagnetism 3: Meissner-Ochsenfeld Effect d. Transition Temperature e. Persistence of Current f. Flux Pinning g. Maglev Train Model"--
"The book will feature a series of practical, investigative, activities which can be used as tutor demonstrations or, more usefully, as student lab' exercises"--
Machine generated contents note: 1. Introduction Resistivity and Conduction in metals History of Superconductivity 2. Superconductivity An explanation of superconductivity The Meissner-Ochsenfeld Effect Diamagnetic Effects Persistence of current Type I and Type II Superconductors Flux Pinning 3. Superconducting Materials Low Temperature Superconductors Organic Superconductors High Temperature Superconductors 4. Applications Medical Imaging CERN Maglev Trains Practical Activities: will be integrated into the text; a-f in section 2 and f and g in section 4 a. Diamagnetism 1: pyrolitic graphite b. Diamagnetism 2: Bismuth c. Diamagnetism 3: Meissner-Ochsenfeld Effect d. Transition Temperature e. Persistence of Current f. Flux Pinning g. Maglev Train Model.
Includes index.
Keywords: Superconductivity -- Study and teaching (Higher) -- Activity programs; TECHNOLOGY & ENGINEERING / Superconductors & Superconductivity